2000
DOI: 10.1002/pds.554
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term safety and tolerability of antihypertensive agents in Korean patients: an observational study

Abstract: The tolerability of antihypertensive medication was highest in Korean patients treated with ARAs, followed by CCBs, beta-blockers, diuretics, alpha-blockers, and ACEIs. The incidences of adverse reactions were different by sex, age and drug class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The CCB are the only first-line drug class that can be initiated without knowledge and timely follow-up of electrolyte status and kidney function, making them a convenient choice when follow-up scheduling is challenging. The vasodilating effects of CCB can cause adverse effects encompassing dizziness, flushing, headache and tibial edema, which women are more likely to experience [ 8 , 24 ]. Calcium-channel blockers, especially nifedipine, are safe to use during pregnancy.…”
Section: Differences In Effects Of Drugs Used In Hypertensionmentioning
confidence: 99%
“…The CCB are the only first-line drug class that can be initiated without knowledge and timely follow-up of electrolyte status and kidney function, making them a convenient choice when follow-up scheduling is challenging. The vasodilating effects of CCB can cause adverse effects encompassing dizziness, flushing, headache and tibial edema, which women are more likely to experience [ 8 , 24 ]. Calcium-channel blockers, especially nifedipine, are safe to use during pregnancy.…”
Section: Differences In Effects Of Drugs Used In Hypertensionmentioning
confidence: 99%
“…The frequency of cough on ACEI is consistently higher in female patients (Os et al 1994, Visser et al 1995, Kim et al 2000, Morimoto et al 2004, Brugts et al 2014, Sato and Fukuda 2015, Alharbi et al 2017. In a pooled analysis of three RCTs comparing perindopril and placebo in 27,492 patients with vascular diseases, older age (≥65 years) and female gender were positively associated with risk of ACEI-induced cough, with adjusted odds ratio (OR) of 1.53 (95 % CI: 1.35 to 1.73) and 1.92 (95 % CI: 1.68 to 2.18), respectively (Brugts et al 2014).…”
Section: Epidemiology Of Acei-induced Coughmentioning
confidence: 99%
“…Moreover, earlier studies showed that the incidence of flushing induced by Ca 2+ channel antagonists is high in middle-aged women (3,4). We previously demonstrated that ovariectomy aggravated nifedipine-induced flushing of tail skin in mice and that this event was blocked by estradiol replacement (5).…”
mentioning
confidence: 99%